Mediating Alghorythm Mediating Da’wa: The New Preacher and Optimization of Social Media for Da’wa in the Case of Habib Ja’far - Nuzul Fitriansyah; Torkis Lubis (Jurnal Penelitian, 2023)
Habib Husein Ja'far, a famous hadrami preacher, is well known for his da'wa, promoting Islam Cinta, and his style of da'wa, which is readily accepted by various circles for his activeness in using various social media platforms to spread his message. As of 2019 when Covid 19 raising his followers on social media is also increasing, he had 1.1 million followers on Instagram, one million followers on Tik-Tok, and also one million subscribers on his Youtube channel named “Jeda Nulis” making him one of the leading social media preachers in Indonesia today. Based on online research and digital observation, this research argues that the algorithms and technical limitations of social media platforms such as Instagram, Twitter, Tik-Tok, and Youtube impact to optimization da’wa on social media. This research will re-question the argument that is da'wa in social media considered superficial and pragmatic due to being conducted by youth Muslims with no religious credential background. Then, what if there is a social media preacher who has a religious education credential that preaches on the same platform? Could other factors, such as technical limitations on specific social media platforms, make da'wa content more general, supraficial and pragmatic? What if a platform that has limited algorithms is used as a first step to attract attention, then is given a more complete understanding by providing the full version of the content on a larger platform like YouTube? This research will focus on how Habib Husein Ja'far, a Hadhrami preacher, descendants of the prophet and has good religious educational background who preaches the da'wa over all social media platforms optimizes his da'wa on social media by utilizing logic, algorithms, and the technical limitations of each platform.